2019
DOI: 10.1002/ca.23483
|View full text |Cite
|
Sign up to set email alerts
|

The Radioulnar Distance at the Level of the Radial Tuberosity

Abstract: Ruptures of the distal biceps brachii tendon are generally treated operatively due to their loss of supination and flexion force. A mechanical impingement at the insertion of the tendon at the radial tuberosity is discussed to play a role in the etiology of this injury. The aim of this study was to present a detailed, three‐dimensional anatomical analysis of the radioulnar space at the radial tuberosity. A total of 166 imprints of the radioulnar space in neutral rotation and pronation from 84 cadaveric specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
0
10
0
4
Order By: Relevance
“…Seiler et al describe a mechanical impingement of the distal biceps tendon during pronation [ 18 ]. Rausch et al [ 20 ] also saw a smaller distance between the radius and the ulna at the radial tuberosity in pronation and suggested this as a risk factor for distal biceps tendon rupture [ 20 ]. The authors argue that mechanical impingement of the radioulnar space could be a significant risk factor for distal biceps tendon ruptures in general and in particular after distal biceps tendon repair [ 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seiler et al describe a mechanical impingement of the distal biceps tendon during pronation [ 18 ]. Rausch et al [ 20 ] also saw a smaller distance between the radius and the ulna at the radial tuberosity in pronation and suggested this as a risk factor for distal biceps tendon rupture [ 20 ]. The authors argue that mechanical impingement of the radioulnar space could be a significant risk factor for distal biceps tendon ruptures in general and in particular after distal biceps tendon repair [ 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rausch et al [ 20 ] also saw a smaller distance between the radius and the ulna at the radial tuberosity in pronation and suggested this as a risk factor for distal biceps tendon rupture [ 20 ]. The authors argue that mechanical impingement of the radioulnar space could be a significant risk factor for distal biceps tendon ruptures in general and in particular after distal biceps tendon repair [ 18 , 20 ]. Heterotopic ossifications could also contribute to mechanical impingement and thus play a role in recurrent ruptures [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of an anatomical reinsertion on the radioulnar space still has to be evaluated and considered when deciding where to reinsert the tendon. 19 , 57 …”
Section: Treatment Of Distal Biceps Tendon Injurymentioning
confidence: 99%
“…In a clinical scenario, postoperative DBT impingement in the RUS may be prevented by avoiding techniques that increase the thickness of the tendon and by using a reattachment site at the proximal aspect of the tuberosity [1]. Raush et al analyzed the radioulnar distance at the level of the radial tuberosity and found that the central zone was the smallest in pronation, and the proximal zone was the smallest in neutral rotation [12].…”
Section: Proximal Radioulnar Spacementioning
confidence: 99%